Peran Pemerintah Dalam Meningkatkan Kesejahteraan Masyarakat Melalui Sektor Peternakan (Studi Kasus: Kecamatan Koto Baru Kabupaten Dharmasraya) - Beni Saputra; Rika Widianita (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Economic development must be carried out continuously by the government and also the community in all economic sectors. This includes the economic development of the livestock sub-sector in the Koto Baru sub-district in Kab. Dharmasraya, animal husbandry is part of the development of the agricultural sector. Production of livestock products is increasing every year but why are the farmers in Koto Baru District not prosperous yet? To get results that can improve people's welfare from the livestock sector, cooperation between the government and breeders is needed in order to achieve the goal of meeting the need for food products, both milk, meat and eggs. The government, through the livestock service, of course, always tries to do its job well, by establishing programs that can help farmers and improve the welfare of breeders. However, prosperity has not been maximized because breeders only want to walk alone, only waiting for the government's hand and do not make the most of government assistance. Of course, for breeders who do things like this it is difficult to achieve prosperity.